Combination of water immersion and carbon dioxide insufflation for minimal sedation colonoscopy: a prospective, randomized, single-center trial - Falt, Přemysl; Liberda, Martin; Smajstrla, Vít; Kliment, Martin; Bártková, Alice; Tvrdík, Josef; Fojtík, Petr; Urban, Ondřej (European journal of gastroenterology & hepatology, 2012)
OBJECTIVE: Water immersion insertion and carbon dioxide (CO2) insufflation, as alternative colonoscopic techniques, are able to reduce patient discomfort during and after the procedure. We assessed whether the combination of water immersion and CO2 insufflation is superior in efficacy and patient comfort to other colonoscopic techniques. METHODS: In a prospective, randomized study, a total of 420 patients were randomized to either water immersion insertion and CO2 insufflation during withdrawal (water/CO2), water insertion and air insufflation during withdrawal (water/air), CO2 insufflation during both insertion and withdrawal (CO2/CO2), or air insufflation during both insertion and withdrawal (air/air). The main outcome was the success of minimal sedation colonoscopy, which was defined as reaching the cecum without switching to another insertion method and without additional sedation beyond the initial 2 mg of midazolam. Patient comfort during and after the procedure was assessed. RESULTS: A total of 404 patients were analyzed. The success rate of minimal sedation colonoscopy in the water insertion arm (water/CO2 and water/air) was 97% compared with 83.3% in the gas insertion arm (CO2/CO2 and air/air; P<0.0001). Intraprocedural pain and bloating were significantly lower in the water/CO2 group than in all other groups. Patient discomfort in the water/CO2 group during 24 h after the procedure was comparable with that in the CO2/CO2 group and significantly lower than that in the air groups (water/air and air/air). No complications were recorded during the study. CONCLUSION: The combination of water immersion and CO2 insufflation appears to be an effective and safe method for minimal sedation colonoscopy. Overall patient discomfort was significantly reduced compared with that in other techniques.
Keywords: spokojenost pacientů; dospělí; insuflace; Abdominal Pain; Female; Immersion; Adult; Patient Satisfaction; ženské pohlaví; ponoření; lidé; Insufflation; analgosedace; Carbon Dioxide; voda; Colonoscopy; Water; prospektivní studie; Conscious Sedation; bolesti břicha; Male; Aged; Flatulence; Prospective Studies; oxid uhličitý; flatulence; kolonoskopie; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans